Microbiomes other than the gut: inflammaging and age-related diseases - Santoro, Aurelia; Zhao, Jiangchao; Wu, Lu; Carru, Ciriaco; Biagi, Elena; Franceschi, Claudio (Seminars in immunopathology, 2020)
During the course of evolution, bacteria have developed an intimate relationship with humans colonizing specific body sites at the interface with the body exterior and invaginations such as nose, mouth, lung, gut, vagina, genito-urinary tract, and skin and thus constituting an integrated meta-organism. The final result has been a mutual adaptation and functional integration which confers significant advantages to humans and bacteria. The immune system of the host co-evolved with the microbiota to develop complex mechanisms to recognize and destroy invading microbes, while preserving its own bacteria. Composition and diversity of the microbiota change according to development and aging and contribute to humans’ health and fitness by modulating the immune system response and inflammaging and vice versa. In the last decades, we experienced an explosion of studies on the role of gut microbiota in aging, age-related diseases, and longevity; however, less reports are present on the role of the microbiota at different body sites. In this review, we describe the key steps of the co-evolution between Homo sapiens and microbiome and how this adaptation can impact on immunosenescence and inflammaging. We briefly summarized the role of gut microbiota in aging and longevity while bringing out the involvement of the other microbiota.